Differential activation of brain areas in children with developmental coordination disorder during tasks of manual dexterity: An ALE meta-analysis. (March 2018) - Fuelscher, I.; Caeyenberghs, K.; Enticott, P.G.; Williams, J.; Lum, J.; Hyde, C.
Highlights: Compromised manual dexterity is a hallmark of the DCD symptom profile. This is the first ALE analysis to detect reliable neural correlates of this symptom. Data suggest differential recruitment of motor systems for manual function in DCD. Interestingly, results may also implicate atypical activation of executive systems. Abstract: Recent neuroimaging studies have reported atypical neural activation in children with Developmental Coordination Disorder (DCD) during tasks assessing manual dexterity. However, small sample sizes and subtle differences in task parameters have led to inconsistent findings, rendering interpretation difficult. The aim of the present meta-analysis was to quantitatively summarize this body of evidence using activation likelihood estimation (ALE) analysis to identify reliable regions of differential neural activation in children with DCD, compared to age-matched controls. Seven studies that adopted f MRI to compare children with and without DCD during manual performance were identified following a literature search. All were included in the ALE analysis. Compared to controls, children with DCD showed reduced activation during a manual dexterity task in the middle frontal gyrus, superior frontal gyrus, cerebellum, supramarginal gyrus, and inferior parietal lobule. Children with DCD showed greater activation in parts of the thalamus. Findings provide much needed clarification into the possible neural contributors to atypical manual dexterity in DCD and highlight the need for neuroimaging studies to include manual performance outcomes.